Two Ottoman documents on Sattar Khan and Baqir Khan’s seeking asylum in the Ottoman consulate at Tabriz - Mortaza (Études sur la Région Méditerranéenne, 2022)
This paper gives a detailed overview of the two documents from the Prime Minister’s Ottoman Archives (BOA), originally written in the Ottoman language, on Sattar Khan and Baqir Khan’s seeking asylum in the Ottoman consulate at Tabriz. In order to understand the documents better, the article begins by reviewing the Ottomans’ policy toward the Iranian constitutional revolution, notably toward Sattar Khan and Baqir Khan as the leaders of the movement in Iran’s Azerbaijan.